APTT (Activated Partial Thromboplastin Time) dan (Prothrombin Time) pada Penderita Diabetes Melitus Tipe 2 di RSUD dr. Doris Sylvanus Palangkaraya - Rinny Ardina; Fera Sartika; Lidya Prihatini Nainggolan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Patients with type 2 diabetes mellitus (T2DM) have a high risk of atherothrombotic events. Hyperglycemia and other metabolic disorders in T2DM are associated with abnormalities of hemostasis system and thrombosis that contribute to cardiovascular disease. Routine laboratory tests to examine the hemostasis system are Activated Partial Thromboplastin Time (APTT) and Prothrombin Time (PT). This study aimed to describe the abnormalities of APTT and PT in patients with T2DM in RSUD dr. Doris Sylvanus Palangkaraya. Twenty subjects with T2DM in RSUD dr. Doris Sylvanus Palangkaraya were obtained using purposive sampling techniques and blood samples were examined with a COATX Biosystem coagulation using photocolorimetric method. This study found that was 70% APTT are shortened, 5% APTT are prolonged and 25% APTT were normal. While the PT results were 25% PT are shortened and 75% APTT were normal. Abnormalities of APTT and PT in T2DM patients in RSUD dr. Doris Sylvanus Palangkaraya showed an abnormality of the coagulation system so as to allow a tendency for bleeding and cardiovascular disease in T2DM patients. Routine coagulation test should be continued to help better diabetes mellitus management in order to prevent micro or macrovascular complications.